2019
DOI: 10.21608/edj.2019.72571
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of emax CAD laminate Veneers cemented with light cure versus dual cure amine free adhesive resin cement (Randomized Controlled Clinical Trial)

Abstract: Statement of the problem The increased thickness of ceramic laminate veneer with butt joint design at the incisal edge reduce the amount of light reaching the cement layer and therefore compromise photo-activation of the luting material However, an adequate cure of the resin-based cement is an important prerequisite for the stability and biocompatibility of the restoration. 57 Dual-cure resin-based cements have been recommended for luting ceramic laminate veneers to compensate for the attenuation of the curing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Yet, the results of color matching in the present study were comparable with some other studies. [11] [39] also found that the e-max CAD veneers revealed a high survival rate in terms of the stability of the color after one year.…”
Section: Hayashi Et Al (2005)mentioning
confidence: 90%
“…Yet, the results of color matching in the present study were comparable with some other studies. [11] [39] also found that the e-max CAD veneers revealed a high survival rate in terms of the stability of the color after one year.…”
Section: Hayashi Et Al (2005)mentioning
confidence: 90%
“…They found that greater microleakage was recorded at the dentine composite resin interfaces than at the enamel/composite resin interfaces. Some studies as done by Elkomy et al in 2019 found that there is no difference in the color stability of veneers when cemented with light or cure modes of the cement [6]. The aim of this study is to evaluate the effect of different curing modes of resin cements: light-cure mode, self-cure mode, and dual-cure mode on the marginal leakage of laminate veneers fabricated on maxillary anterior teeth using heat pressed ceramic.…”
Section: Introductionmentioning
confidence: 90%